Local activation of light-induced degradation in co-doped boron-phosphorus silicon: Evidence of defect diffusion phenomena. (15th November 2021) - Najjar, M.; Dridi Rezgui, B.; Bouaicha, M.; Palais, O.; Bessais, B.; Aouida, S.
Abstract: This study is interested in the local activation of Light-induced degradation (LID) defect in highly co-doped silicon wafers with boron and phosphorus. For this purpose, the experiments are focused on measuring the minority carrier lifetime before and after LID activation via a mapping technique. The LID defect density exhibits a Gaussian distribution centered on the excitation point of the laser beam; the intensity of the Gaussian distribution of the LID defect varies with the concentration of the co-dopants. The lifetime of the minority carriers decreases in all-silicon sample regions, while the excitation laser beam focuses on an area of approximately one mm 2 . This observation indicates that LID defects are activated even in the unexcited areas of silicon wafers, suggesting a LID diffusion phenomenon from the laser excitation point to the whole silicon wafer. We deduce that a high phosphorus doping level in silicon wafers leads to a significant reduction in the LID effect.